2020
DOI: 10.1002/masy.201900149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight, Degree of Deacetylation, and Acute Oral Toxicity Evaluation of Irradiated and Nonirradiated Chitosan Using Mice

Abstract: Chitosan has been used as antimicrobial, anti‐fungal, anti‐virus, antioxidant, and anti‐cancer agent. As a new biomaterial, chitosan will be required to undergo certain toxicity tests for biocompatibility and safety assessment; one of the requirements is acute toxicity. In this study, nonirradiated and irradiated chitosan is used. The MW of chitosan is analyzed using GPC. The degree of deacetylation (DD) is measured by FTIR. OECD Guideline for Testing of Chemicals No 423 is used for evaluation of acute oral to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…The percentage value of molecular weight reduction in this study was higher than the previous research 20 , due to the addition of H2O. Meanwhile, the percentage value of molecular weight loss carried out in this study was lower than the study of Hien et al 11 which used the addition of H2O2..…”
Section: Chitosan Degradation Results and Purification Of Degraded Ch...contrasting
confidence: 74%
See 1 more Smart Citation
“…The percentage value of molecular weight reduction in this study was higher than the previous research 20 , due to the addition of H2O. Meanwhile, the percentage value of molecular weight loss carried out in this study was lower than the study of Hien et al 11 which used the addition of H2O2..…”
Section: Chitosan Degradation Results and Purification Of Degraded Ch...contrasting
confidence: 74%
“…Permeation Chromatography (GPC) 20 The molecular weight of the degraded chitosan was characterized by GPC using Pullulan (Lot: BCCB4132) as standard to obtain the calibration curve. Chitosan sample preparation was carried out by dissolving chitosan (1 mg) in 1 ml of acetate buffer (0.5 M CH3COOH/0.5 M CH3COONa) for one night, then the samples were mixed using vortex, incubated (50°C, 60 mins) then centrifuged at 10.000 rpm for 10 mins.…”
Section: Determination Of Molecular Weight By Gelmentioning
confidence: 99%
“…For example, rapeseed (Brassica chinensis) exhibits favorable germination index, seedling growth, and root length when coated with LMWC [83]. In a similar way, Darwis et al [148] demonstrated that chitosan with an avg. MW of 141,000 Da and 14,000 Da respectively, both were effectively used on beans, potatoes, and chili to increase crop yields and reduce disease caused by virus, bacteria, and fungi.…”
Section: Low-molecular-weight Chitosanmentioning
confidence: 94%
“…Chitosan powder was packed in polyethelene plastics 20x20 cm 2 . Chitosan is irradiated using a Co-60 γ-radiation source with an activity 53.13 kCi and 75 kGy absorbed dose [1] in a natural rubber irradiator (IRKA) at the Research Center for Radiation Process Technology (PRTPR), National Research and Innovation Agency, BRIN, Jakarta, Indonesia.…”
Section: Chitosan Irradiationmentioning
confidence: 99%